Magneto-Fluid Dynamics Fundamentals and Case Studies of Natural Phenomena - Lorrain, Paul; Lorrain, Francois; Houle, Stephane (Astronomy and Astrophysics Library, 2006)
This book concerns the generation of electric currents and of electric space charges inside conducting media that move in magnetic fields. The authors postulate nothing but the Maxwell equations. They discuss at length the disk dynamo, which serves as a model for the natural self-excited dynamos that generate magnetic fields such as that of sunspots. There are 36 Examples and 13 Case Studies. The Case Studies concern solar phenomena -- magnetic elements, sunspots, spicules, coronal loops -- and the Earth's magnetic field.